2015
DOI: 10.3390/molecules20046941
|View full text |Cite
|
Sign up to set email alerts
|

NKCS, a Mutant of the NK-2 Peptide, Causes Severe Distortions and Perforations in Bacterial, But Not Human Model Lipid Membranes

Abstract: NKCS is an improved mutant of the bioactive peptide NK-2, which shows strong activity against Escherichia coli and low toxicity towards human cells. The different activity demonstrates the relevance of the physico-chemical nature of the target membrane for the biological effect of this peptide. We studied the effect of this potent antimicrobial peptide on model membranes by activity studies, differential scanning calorimetry, single molecule tracking and tracer efflux experiments. We found that NKCS severely d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…We observed PS‐dependent enhanced peptide binding to (Zeta potential measurements) as well as peptide insertion into (Trp fluorescence analysis) lipid model membranes constituted of zwitterionic PC and PS, reflecting the outward‐facing leaflet of cancer human cells. This is fully compliant with various former investigations where only minor to completely absent interactions of peptide NK‐2 with pure PC model membranes have been repeatedly proven . This is in contrast to melittin, where no such dependence could be observed.…”
Section: Discussionsupporting
confidence: 91%
“…We observed PS‐dependent enhanced peptide binding to (Zeta potential measurements) as well as peptide insertion into (Trp fluorescence analysis) lipid model membranes constituted of zwitterionic PC and PS, reflecting the outward‐facing leaflet of cancer human cells. This is fully compliant with various former investigations where only minor to completely absent interactions of peptide NK‐2 with pure PC model membranes have been repeatedly proven . This is in contrast to melittin, where no such dependence could be observed.…”
Section: Discussionsupporting
confidence: 91%
“…TAT peptide, a typical CPP, did not translocate the GUVs containing zwitterionic PC lipids in the same experimental conditions, although it was highly positively charged, with six arginine and two lysine amino acid residues. However, HIV1 TAT accumulated on neutral membranes as in the case of the cyclic LyP‐1 peptide while tLyP‐1 showed neither accumulation nor internalization in PC membranes, similar to antimicrobial peptides …”
Section: Discussionmentioning
confidence: 93%
“…However, HIV1 TAT accumulated on neutral membranes as in the case of the cyclic LyP-1 peptide while tLyP-1 showed neither accumulation nor internalization in PC membranes, similar to antimicrobial peptides. 31 To get further insight into the role played by lipid composition on the mode of action of the investigated peptides on model membranes, we incubated either tLyP-1 or LyP-1 peptides with anionic GUVs containing different percentages of DOPS. Experimental results showed that tLyP-1 peptide strongly accumulated on the membranes and the accumulation was higher than in case of LyP-1 (Figures 2, 4B, and S2).…”
Section: Cargo Delivery By Tlyp-1 Peptidesmentioning
confidence: 99%
“…PEs are reported to have HLB values around 6, while PGs’ HLB values are even lower [ 27 , 28 ]; hence their mixtures are expected to have HLB values which would promote their use as inverted emulsion stabilizers. Moreover, the PLs mixture employed is characterized by a thermotropic phase transition of the lipid microscopic arrangement from a gel phase to a fluid liquid crystalline phase at 18 °C [ 29 ]. Therefore, at 25 °C (i.e., our experimental temperature), PLs are in a fluid liquid crystalline phase thus potentially providing a major stability by wrapping the dispersed emulsion droplets in a viscous liquid crystalline matrix [ 30 ].…”
Section: Resultsmentioning
confidence: 99%